PENGARUH UKURAN PERUSAHAAN, RASIO LEVERAGE, INTENSITAS MODAL, DAN LIKUIDITAS PERUSAHAAN TERHADAP KONSERVATISME PERUSAHAAN (Studi pada Perusahaan yang Belum Menggunakan IFRS) - Willyza Purnama H; Daljono Daljono (Diponegoro Journal of Accounting, 2013)
This study aims to examine the influence of firm size, leverage ratio, capital intensity, and liquidity for corporate conservatism. Corporate conservatism is a dependent variable in this study that measured by non operating accrual. Independent variable in this study are firm size, leverage ratio, capital intensity, and liquidity. The samples of this research are the manufacturing firms that taken randomly and listed in Indonesian Stock Exchange in 2008 -2010. The samples are collected using random sampling method and resulted 82 firms become the samples. Hyphoteses testing using OLS (Ordinary Least Square) regression analysis.By using proxy non operating accrual for corporate conservatism, the result of the research indicates different result from previous research. Therefore, this study conclude that firm size, and capital intensity affect the corporate conservatism significantly. But leverage ratio and liquidity don’t affect the corporate conservatism significantly. Seen by simultaneous test, this study also proves that firm size and capital intensity have big contribution in affecting corporate conservatism. And corporate is consistently decreasing asset and income to be more conservative than increasing liability and cost.